Updating contextualized clinical practice guidelines on stroke rehabilitation and low back pain management using a novel assessment framework that standardizes decisions. (December 2015) - Gambito, Ephraim; Gonzalez-Suarez, Consuelo; Grimmer, Karen; Valdecañas, Carolina; Dizon, Janine; Beredo, Ma.; Zamora, Marcelle
Abstract Background Clinical practice guidelines need to be regularly updated with current literature in order to remain relevant. This paper reports on the approach taken by the Philippine Academy of Rehabilitation Medicine (PARM). This dovetails with its writing guide, which underpinned its foundational work in contextualizing guidelines for stroke and low back pain (LBP) in 2011. Methods Working groups of Filipino rehabilitation physicians and allied health practitioners met to reconsider and modify, where indicated, the 'typical' Filipino patient care pathways established in the foundation guidelines. New clinical guidelines on stroke and low back pain which had been published internationally in the last 3 years were identified using a search of electronic databases. The methodological quality of each guideline was assessed using the iCAHE Guideline Quality Checklist, and only those guidelines which provided full text references, evidence hierarchy and quality appraisal of the included literature, were included in the PARM update. Each of the PARM-endorsed recommendations was then reviewed, in light of new literature presented in the included clinical guidelines. A novel standard updating approach was developed based on the criteria reported by Johnston et al. (Int J Technol Assess Health Care 19(4):646–655, 2003) and then modified to incorporate wording from the foundational PARM writing guide. The new updating tool was debated, pilot-tested and agreed upon by the PARM working groups, before being applied to the guideline updating process. Results Ten new guidelines on stroke and eleven for low back pain were identified. Guideline quality scores were moderate to good, however not all guidelines comprehensively linked the evidence body underpinning recommendations with the literature. Consequently only five stroke and four low back pain guidelines were included. The modified PARM updating guide was applied by all working groups to ensure standardization of the wording of updated recommendations and the underpinning evidence bases. Conclusions The updating tool provides a simple, standard and novel approach that incorporates evidence hierarchy and quality, and wordings of recommendations. It could be used efficiently by other guideline updaters particularly in developing countries, where resources for guideline development and updates are limited. When many people are involved in guideline writing, there is always the possibility of 'slippage' in use of wording and interpretation of evidence. The PARM updating tool provides a mechanism for maintaining a standard process for guideline updating processes that can be followed by clinicians with basic training in evidence-based practice principles.